PELAYANAN MASYARAKAT AKIBAT COVID-19 DI KABUPATEN CIANJUR DALAM PERSPEKTIF KEBIJAKAN WORK FROM HOME (WFH) BERDAMPAK TERHADAP PELAYANAN PUBLIK (Universitas Suryakancana, 2021)
Since the Covid-19 pandemic broke out in Indonesia in general and the jurisdiction of Cianjur Regency in particular, the necessity of maintaining physical distance or physical distancing has forced many people to stay at home. Working from home or Work from Home (WFH) has become a new norm and habit that must be carried out by all parties in various sectors. If calculated since the Covid-19 case first appeared in early February 2020 ago, it has been almost a year since the Work from Home recommendation has been in effect.Keywords : Covid-19, Cianjur Regency, Public Service, Work From Home (WFH).